2013
DOI: 10.1016/j.apmr.2012.09.016
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary Examination of the Relation Between Participation and Confidence in Older Manual Wheelchair Users

Abstract: Objective-To examine the relationship between frequency of participation and confidence with using a manual wheelchair among community-living, older wheelchair users, and the moderating effect of sex. Design-Cross-sectional Setting-CommunityParticipants-54 participants who were community-living manual wheelchair users (65% male), were ≥50 years of age (mean = 59 years), used their wheelchair daily, and had ≥6 months experience with using a wheelchair. Intervention-NoneMain Outcome Measures-The 16-item Late Lif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
20
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 8 publications
1
20
1
Order By: Relevance
“…The WheelCon-M has predictive validity in older, community-living, manual wheelchair users. 21 Support for the reliability and validity of the WheelCon-M have also been reported in other studies with samples partially comprised of older adults. 19,23 Because of the potential for confounding, information on depression and anxiety symptoms, risk taking behaviour, and wheelchair skills were collected.…”
Section: Measurementsupporting
confidence: 59%
See 3 more Smart Citations
“…The WheelCon-M has predictive validity in older, community-living, manual wheelchair users. 21 Support for the reliability and validity of the WheelCon-M have also been reported in other studies with samples partially comprised of older adults. 19,23 Because of the potential for confounding, information on depression and anxiety symptoms, risk taking behaviour, and wheelchair skills were collected.…”
Section: Measurementsupporting
confidence: 59%
“…21 This finding is significant because it was observed after controlling for ability to use a wheelchair, thereby suggesting that low confidence may be a barrier to participation among older wheelchair users regardless of their ability to use their wheelchair. The authors concluded that because the confidence-participation relationship was moderated by sex, treatment strategies to address low confidence may be especially important for older male wheelchair users when attempting to increase their frequency of participation in social and personal roles.…”
Section: Cihr Author Manuscriptmentioning
confidence: 92%
See 2 more Smart Citations
“…Evidence using Classical Test Theory methods indicates that the WheelCon measurements are both reliable and valid in manual wheelchair-users. 2 Furthermore, research using the WheelCon has shown that lower self-efficacy is associated with lower levels of participation frequency 3,4 and life-space mobility 5 in wheelchair-users aged 50 and older.…”
mentioning
confidence: 99%